Plankton Community Structure in Seagrass Beds at Selangan Hamlet, Bontang City, East Kalimantan - Imran, Muhammad Ali; Sari , Lily Inderia; Nurfadillah , Nurfadillah (Faculty of Fisheries and Marine Science, Mulawarman University, 2024)
Plankton is an organism that lives floating in the water whose movement is influenced by the current. The presence of plankton in a water body can be used as a bioindicator because it has a high level of sensitivity and is also influenced by changes in water conditions. Changes in water conditions can be caused by human activities. The purpose of this study was to determine the structure of the plankton community in seagrass beds in the waters of Selangan Hamlet. This research was conducted in November-December 2019 in Selangan Hamlet, Bontang City, East Kalimantan. Data analysis includes abundance, diversity index, uniformity index and dominance index. The results showed that the composition of plankton species found in the waters of Selangan Hamlet at 4 stations with conditions at high tide and low tide obtained 13 plankton classes namely Cyanophyceae, Bacillariophyceae, Oligotrichea, Dinophyceae, Foraminifera, Chlorophyceae, Trebouxiophyceae, Conjugatophyceae, Hexanauplia, Crustaceae, Gastropoda, Tubulinea, and Euglenoidea consisting of 47 plankton species. Plankton abundance ranged from 893-2,514 ind/L. The structure of the plankton community in the waters of Selangan Hamlet has a Diversity Index (H') value in the medium category with a range of values of 2.28-2.99, Diversity Index (E) category of stable plankton communities with a range of values of 0.82-0.95, and Dominance Index (C) category there is no dominant genus at each research station with a range of values of 0.06-0.14.